Key international themes in coercion - Molodynski, A; O'Brien, A; Burns, J (Cambridge University Press, 2018)
Coercion remains a dominant theme in mental healthcare and a source of major concern. While the presence of coercion is ubiquitous internationally, it varies significantly in nature and degree in different countries and is influenced by a variety of factors. Recent reports have raised concerns about physical restraint and the increasing use of legislation in high-income countries. At the same time, a recent Human Rights Watch report on pasung (the practice of tying or restricting movement more generally) in Indonesia has served to highlight the plight of many in middle- and lower-income countries who are subject to degrading and dehumanising ‘treatment’.